The emancipatory potential of extinction accounting: Exploring current practice in integrated reports. Issue 1 (1st March 2018) - Maroun, Warren; Atkins, Jill
Abstract: This paper adopts a normative approach to develop a dynamic form of corporate reporting designed to deal with the threat posed by mass extinction of species. The proposed reporting framework is intended to show how a type of accounting – which is referred to as extinction accounting – can and should be used to drive positive corporate change and prevent the loss of species. The framework is inspired by both an anthropocentric and deep ecological view on nature and draws on accountancy's emancipatory potential rather than attempting to find a substitute for current technologies of accounting and accountability. The prior literature on biodiversity and emancipatory accounting is complemented by showing how an innovative form of reporting on a specific environmental issue can be operationalised and used in the short-term to respond to the threats posed by mass extinction.